Anthropogenic disturbance modifies tree functional traits in the only remnant swamp forest of Bangladesh - Khan, Ariful; Karim, Md Rezaul; Mohammed,; Kibria, Mohammad Golam; Sinha, Karishma; Sultana, Fahmida; Mukul, Sharif A.; Arfin-Khan, Mohammed A. S. (Frontiers in Ecology and Evolution, 2023)
The relationship between ecosystem functions and plant functional traits has been well documented and is considered to be one of the most vital topics in ecology. However, the correlation between anthropogenic disturbance and tree functional trait diversity remains largely unclear. The present study investigates the role of anthropogenic disturbance on selected tree functional traits in Ratargul Swamp Forest (RSF)the only remnant tropical freshwater swamp forest ecosystem in Bangladesh. We established fifty plots and collected six plant traits, i.e., tree height, specific leaf area (SLA), wood density (WD), leaf dry matter content (LDMC), seed mass, and bark-thickness. Two-way analysis of variance (ANOVA) was carried out to test the interaction between plant functional traits and anthropogenic disturbance in RSF. Our study found that anthropogenic disturbance has a significant (p < 0.05) influence on deciduous swamp forest tree species functional traits but none on evergreen tree species functional traits. For deciduous trees, disturbance has a significant positive effect on CWM.SLA (p < 0.05) and CWM.Height (p < 0.05) and a negative impact on CWM.Barkthickness and CWM.Seed-mass (p < 0.05). There were no significant effect of disturbance on CWM.WD and CWM.LDMC. We believe, the present study will contribute towards improving our understanding of the effect of disturbances on tree functional trait diversity in tropical human dominated landscapes where anthropogenic pressure are increasing at an unprecedented rate. It will also function as an essential for conservation related decision-making of Ratargul Swamp Forest in northeastern Bangladesh, and elsewhere in the tropics with a similar context.